Arsenic removal from water employing a combined system: photooxidation and adsorption - Lescano, Maia Raquel (2015)
A combined system employing photochemical oxidation (UV/H2O2) and adsorption for arsenic removal from water was designed and evaluated. In this work, a bench-scale photochemical annular reactor was developed being connected alternately to a pair of adsorption columns filled with titanium dioxide (TiO2) and granular ferric hydroxide (GFH). The experiences were performed by varying the relation of As concentration (As (III)/As (V) weight ratio) at constant hydrogen peroxide concentration and incident radiation. Experimental oxidation results were compared with theoretical predictions using an intrinsic kinetic model previously obtained. In addition, the effectiveness of the process was evaluated using a groundwater sample. The mathematical model of the entire system was developed. It could be used as an effective tool for the design and prediction of the behaviour of these types of systems. The combined technology is efficient and promising for arsenic removal to small and medium scale.